Corporate investment in artificial intelligence: The role of GDP, ICT exports, and patents - Rahman Md. Shanur; Golder Uttam; Ghosh Prosenjeet (Journal of Economics and Management)
– Despite the widespread use of artificial intelligence (AI) in fields as diverse as finance, healthcare, and education, little is known about the factors motivating its financing. This study investigates the drivers influencing corporate investment in AI using global data from 2013 to 2022, focusing on the relationship between GDP growth, ICT goods exports, AI patent applications (AIPA), and regulatory quality with corporate AI investments.